Managing Birth Asphyxia: Helping Babies Breathe. Issue 1 (January 2016) - Callister, Lynn Clark
Abstract : Helping Babies Breathe (HBB) is a remarkable evidence-based intervention with documented significant outcomes. It is a neonatal resuscitation program embedded within essential services for mothers and newborns in partnership with the American Academy of Pediatrics, the World Health Organization, United States Agency for International Development, Save the Children's Saving Newborn Lives program, the National Institute of Child Health and Development, and other global health stakeholders. Our global health expert, Dr. Callister, provides an overview of the program.